Adverse events associated with COVID-19 vaccination among health care professionals of Himachal Pradesh- a Rapid Survey. - Singh, Harshvardhan; Sharma, Shailja (Indian Journal of Community Health, 2021)
Background: The rolling out of the COVID -19 vaccination programme was accompanied by several doubts including the safety and occurrence of adverse effects after the vaccination. Methodology: A cross sectional study was conducted amongst the health care professionals working in the state of Himachal Pradesh to assess the frequency and types of side effects associated with the administration of Covid-19 vaccines using a semi structured questionnaire floated through a Google form. Result: Of the 187 responses received, after the 1st dose, 37.5% participants reported malaise, 31% myalgia, 36.4% low-grade fever, while 18.5% high-grade fever. Mild reactions at the injection site were reported by 37.5%, headache was reported by 3%, low back ache, drowsiness, giddiness and diarrhea were reported by about 3%. No reactions were reported by 18.5% of the participants. After the second dose, 51.8% did not report any adverse event, 17.1% reported malaise,15.2% reported low grade fever, 3% reported high grade fever, 20.1% reported mild reactions at the site of injection while 4.2% reported drowsiness, breathlessness on exertion, nausea, low back ache and diarrhea. Conclusion: The frequency of adverse events with COVID -19 vaccines is not higher than those observed with other commonly used vaccines.